Long-term Oncologic Outcomes After Neoadjuvant Radiation Therapy for Retroperitoneal Sarcomas. Issue 1 (July 2015) - Nussbaum, Daniel P.; Speicher, Paul J.; Gulack, Brian C.; Ganapathi, Asvin M.; Englum, Brian R.; Kirsch, David G.; Tyler, Douglas S.; Blazer, Dan G.
Abstract : Objective: To evaluate long-term survival among patients undergoing radiation therapy (RT), followed by surgical resection of retroperitoneal sarcomas (RPS). Background: Despite a lack of level 1 evidence supporting neoadjuvant RT for RPS, its use has increased substantially over the past decade. Methods: The 1998–2011 National Cancer Data Base was queried to identify patients who underwent resection of RPS. Subjects were grouped by use of neoadjuvant RT. Perioperative variables and outcomes were compared. Multivariable logistic regression was performed to assess predictors of neoadjuvant RT. Groups were propensity matched using a 2:1 nearest neighbor algorithm and short-term outcomes were compared. Finally, long-term survival was evaluated using the Kaplan-Meier method, with comparisons based on the log-rank test. Results: A total of 11, 324 patients were identified. Neoadjuvant RT was administered to 696 patients (6.1%). During the study period, preoperative RT use increased from 4% to nearly 15%. Male sex, tumor size larger than 5 cm, treatment at an academic/research program, and higher tumor grade all predicted neoadjuvant RT administration. After propensity matching, the only difference in baseline characteristics was the use of neoadjuvant chemotherapy. Although neoadjuvant RT was associated with a higher rate of negative margins (77.5% vs 73.0%; P = 0.014), there was no corresponding improvement in 5-year survival (53.2% vs 54.2%; P = 0.695). Conclusions: Despite the increasing use of neoadjuvant RT for patients with RPS, the survival benefit associated with this treatment modality remains unclear. Continued investigation is needed to better define the role of RT among patients with RPS. Abstract : The use of neoadjuvant radiation therapy for retroperitoneal sarcomas has increased substantially despite a lack of level 1 evidence, suggesting a survival benefit. Here, we provide the largest study to date, evaluating the long-term oncologic outcomes associated with preoperative radiation therapy, followed by surgical resection of retroperitoneal sarcomas.